Influence of the Robotic Milking System on Milk Production and Quality: Systematic Review - Grazziotin, Rodrigo Chaves Barcellos; Rutz, Fernando; Vieira, Daniel José Cavalli; Silva, Vitoria Mendonça da; Chiesini, Rodrigo Garavaglia; Viegas, Julio; Bermudes, Rogério Folha (Journal of Agricultural Studies, 2022)
This review aims to report the direct influence of a robotic milking system (RMS) on milk production and quality. The Scopus, SciELO, and Web of Science platforms were used as search databases. We followed the PRISMA protocol for the identification and screening of articles. Initially, 336 articles were identified. We excluded 186 articles for duplicity, 53 after screening abstracts and titles, 20 for lack of access, and 58 articles based on the exclusion criteria. Nineteen articles from 2002 to 2021 from 10 different journals were selected. We observed an increase in publications related to RMS in recent years, and the Journal of Dairy Science gained prominence among the journals whose articles were used in the present study. After lexicographic analysis of abstracts, it was clear that there were five predominant classes, and the keyword RMS was more associated with factors related to cows than milk. The study results contribute to a greater understanding of RMS research, providing farmers and readers with clarification on the actual influences on the dairy chain system and future research projects.